ANALISIS VALUE ENGINEERING PADA PEMBANGUNAN RUMAH SAKIT UMUM DAERAH SAYANG IBU BALIKPAPAN - Joko Riyanto; Kartono Wibowo; Moh Faiqum Niam (Media Bina Ilmiah, 2023)
Sayang Ibu Hospital in Balikpapan, according to the data of the design planning, according to the plan of improvement and development into a category C hospital, the budget is Rp. 167,131,551,076.45 of considerable budget value, prior to construction tenders, a value engineering analysis was performed to obtain a better/lower budget plan than the initial plan with functional limitations and quality of work without compromising quality, reliability value and features with the highest net benefit value. From the Value Engineering analysis with the initial design (A0) and three design alternatives to get best design, obtained in the third alternative design (A3), that is, the results of Use of Wharf Structures in the Back Zone Area can be concluded to have It is recommended to design the components with the lowest cost efficiency up to Rp. Save Rs 164,066,582,357.48 in construction cost. 3,064,068,634.72 accounting for 1.83%, the highest net benefit value is in line with hospital planning review standards and building technology planning standards